The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/mmr.2015.3768
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of triple drug resistant head and neck squamous cell carcinoma cell lines

Abstract: Resistance to chemotherapy leading to poor outcome and survival remains a challenge for developing strategies for therapeutic interventions in all types of cancer, including head and neck cancer. In vitro chemoresistant cell line models are an indispensable resource towards delineating the mechanisms involved in drug resistance/response and for the development of novel drugs. Current treatment for head and neck cancer includes chemotherapy with cisplatin, docetaxel and 5-fluorouracil (5-FU) and the response ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…It is worth noting that multidrug cross-resistance mechanisms possibly occur on HNC cells. As previously reported, triple drugs (docetaxel, cisplatin, and 5−FU) −resistant HNSCC cell lines (Hep−2 and CAL−27) exhibited higher chemotherapy resistance, reduced apoptotic cell death, and an increased expression of MDR1, MRP2, ERCC1, CTR, Survivin, and TS (88), which suggests that multiple drug-resistant HNSCC cells can simultaneously have multidrug cross-resistance mechanisms, including DNA/RNA damage repair, drug efflux, and apoptosis inhibition.…”
Section: Paclitaxel/docetaxelsupporting
confidence: 69%
“…It is worth noting that multidrug cross-resistance mechanisms possibly occur on HNC cells. As previously reported, triple drugs (docetaxel, cisplatin, and 5−FU) −resistant HNSCC cell lines (Hep−2 and CAL−27) exhibited higher chemotherapy resistance, reduced apoptotic cell death, and an increased expression of MDR1, MRP2, ERCC1, CTR, Survivin, and TS (88), which suggests that multiple drug-resistant HNSCC cells can simultaneously have multidrug cross-resistance mechanisms, including DNA/RNA damage repair, drug efflux, and apoptosis inhibition.…”
Section: Paclitaxel/docetaxelsupporting
confidence: 69%
“…A common drug cocktail employed in HNC chemotherapy due to its potential synergistic effect is the combination of cisplatin, docetaxel, and 5-FU. To elucidate some of the mechanisms behind drug resistance triggered by this drug combination, triple-drugresistant cell lines were generated by exposing the cell lines to increasing drug concentrations [44]. The study aimed to evaluate both cellular and molecular effects by assessing cell viability, cell cycle properties, apoptosis, and gene expression associated with multidrug resistance.…”
Section: Pharmacomics-towards Personalised Chemotherapymentioning
confidence: 99%
“…Table 2 is a compilation of gene mutations responsible for chemotherapy resistance. [44] Critical role within the nucleotide excision repair system of DNA Excision repair cross-complementation group 4 XPF (ERCC4) (Vaezi et al, 2011) [46] Protein involved in DNA binding and protein-protein interaction Lumican (LUM) (Yamano et al, 2010) [41] Proteoglycan involved in epithelial cell migration and tissue repair Cyclic nucleotide phosphodiesterase type 3 (PDE3B) (Yamano et al, 2010) [41] Intracellular messengers that regulate numerous signalling pathways Platelet-derived growth factor C (PDGF-C) (Yamano et al, 2010) [41] Important role in connective tissue growth and function. Belongs to the PDGF/vascular endothelial growth factor family Next to drug resistance, chemotoxicity is another factor limiting the success of chemotherapy.…”
Section: Pharmacomics-towards Personalised Chemotherapymentioning
confidence: 99%
“…Studies have shown that 95% of the LSCC has poor sensitivity to chemotherapy. Thus, treatment of LSCC is largely ineffective due to the resistance of the tumor cells to chemotherapy (Govindan et al, 2015). However, the resistance mechanism of LSCC cells is still unclear and the corresponding effective way to suppress drug resistance is also elusive.…”
Section: Introductionmentioning
confidence: 99%